2016
DOI: 10.1089/acm.2015.0299
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Gait Balance and Brain Connectivity in Response to Equine-Assisted Activity and Training in Children with Attention Deficit Hyperactivity Disorder

Abstract: EAAT may improve clinical symptoms, gait balance, and brain connectivity, the last of which controls gait balance, in children with ADHD. However, children with ADHD who have deficits in the fronto-cerebellar tract did not exhibit changes in brain connectivity as extensive as those in healthy children in response to EAAT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 45 publications
1
36
0
7
Order By: Relevance
“…Surprisingly, the significant difference was that ASD children used more complete ellipsis device for the introduction of "the boy" character in comparison to TD children; while, this type of character reference introduc-ing was not observed in TD children's narratives. This finding can support the evidence that, because of some deficits in attention, children with ASD are more likely to produce ambiguous references than TD peer groups [25,38]. It can also be related to attention, memory and pragmatics deficits, which is partly in line with Tager-Flusberg's [44] claim.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Surprisingly, the significant difference was that ASD children used more complete ellipsis device for the introduction of "the boy" character in comparison to TD children; while, this type of character reference introduc-ing was not observed in TD children's narratives. This finding can support the evidence that, because of some deficits in attention, children with ASD are more likely to produce ambiguous references than TD peer groups [25,38]. It can also be related to attention, memory and pragmatics deficits, which is partly in line with Tager-Flusberg's [44] claim.…”
Section: Discussionsupporting
confidence: 82%
“…Despite some similarities in language abilities [25,37,38], various studies reported a wide variety of linguistic differences and impairments for children with ASD [39][40][41], particularly in the discursive and pragmatic aspects, in which various kinds of rules and processes govern the contextual suitability of language [42][43][44][45][46]. Some literature on referential choices made by children with ASD proposed that, due to impairments in attention, working memory, mental processes and difficulties in using pronouns, they tended to adhere their narratives to the explicit referential expressions such as full lexical noun phrases [18,47].…”
Section: Persian Referential Expressionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Hyun study that used TMS to stimulate the brain of children with ADHD, it was found that the brain neurophysiological parameters of the children with ADHD is different with others. Despite the few studies in this field, regarding the high homogeneity of the results, and considering the high difference in volume of neurotransmitters, lower levels of cortical inhibition in children with ADHD can be observed compared to healthy children [17,18]. Zang (2002) by studying 38 children with ADHD, reported that clinical symptoms and balance of walking in children with ADHD improved after four weeks of horse riding program.…”
Section: Brain Dysfunctionmentioning
confidence: 99%